Writing new letters : a commentary on the correspondence of St Paulinus of Nola (c.348-431 A.D.) with Ausonius of Bordeaux : Carmina 10 and 11 - Janse van Rensburg, Cornelius Marthinus; Paulinus,of Nola, Saint,ca. 353-431 (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1996.